RISIKO BENCANA DI KABUPATEN PEKALONGAN (DISASTER RISK IN PEKALONGAN REGENCY) - Aji, Ananto; Sidiq, Wahid Akhsin Budi Nur; Nugraha, Satya Budi; Setyowati, Dewi Liesnoor; Martuti, Nana Kariada Tri (Jurnal Geografi, 2016)
Pekalongan Regency of Central Java is a region with high risk of disaster. Various kinds of disaster such aslandslide, flood, drought, and tidal flood have somehow become âseasonal customerâ for occurring inPekalongan Regency. This research aimed to prepare the mapping of disaster risk in order to strengthen theefforts in reducing disaster risk in Pekalongan Regency. The research method applied in this research refers tothe Headâs Regulation of National Risk Management Agency Number 2/2012. Since the risks of tidal flood werenot yet included in the regulation, the field observation approach was used in this research. The analysis ofdisaster risk also considered the collecting method of disaster history by organizing focus group discussion(FGD) with the related parties. The research result showed that there were high risks of flood disaster coveredsome sub-districts such as Kajen, Kesesi, Wonopringgo, Karangdadap, Tirto, Wiradesa and Wonokerto; therewere twenty six villages in total. High risk of landslide potentially occurred in large part of villages on the southarea of Pekalongan Regency. High risk of drought was relatively evenly spread in the center area. Lastly, highrisk of tidal flood potentially occurred in fifteen villages along side of Java Sea.